Contaminação de mercúrio em itens alimentares na dieta de atuns do Atlântico Oeste Equatorial - Moraes, Cyntia Rafaela Ferreira de (2021)
In this work, in the first chapter, we discuss the main concepts related to Hg contamination in fish and fish products, the consequent risk associated with human exposure and food security. Among the analytical methodologies for reducing Hg contamination and its toxicity, we highlight the use of chelating agents such as cysteine and EDTA, as promising. We also highlight the relevance that variables such as pH, temperature and preparation time have in preparation methods for consumption, such as cooking and frying processes, which can significantly contribute to the reduction of Hg in fish. We also highlight the importance of adopting techniques that allow an objective understanding on the part of the consumer, proposing the use of health quotients (HQ) regarding the assessment of the risk of Hg contamination by eating fish. In the second chapter, we analyze the isotopic composition, the relative contribution rates and total Hg loads in the food items that make up the diet of two tuna species (Thunnus albacares and Thunnus obesus) captured in oceanic regions of the Equatorial West Atlantic.We found that the main type of item preyed upon by both species throughout the study period was fish, with a 70.1% contribution to the diet of T. albacares and a 71.3% contribution to the diet of T. obesus. Fish from the families Bramidae, Exocoetidae and Howellidae had the highest concentrations of total Hg. We concluded, based on the food ecology of the tuna studied, that the highest rates of food contribution were related to items with high Hg content. We also conclude that the risk quotient (HQ) indexes calculated (based on scientific literature) for the species of tuna T. albacares (0.172) and T. obesus (0.590) indicated that exposure is unlikely to cause consumer health. Thus, this index can be adopted by consumers as a preventive measure regarding the risk of consuming fish that are liable to contamination by metals. In the third chapter, we determined the total length x Hg ratios in two species of epipelagic fish, Diodon eydouxii and Hirundichthys affinis and the species of mesopelagic fish, Howella atlantica from the Brazilian Equatorial West Atlantic. The concentration of Hg varied according to the maturation stage in at least two of the four species studied, H. affinis and H. atlantica.